Development of RAPD-PCR assay for identifying Holstein, Angus, and Taiwan Yellow Cattle for meat adulteration detection - Lin, Chin-Cheng; Tang, Pin-Chi; Chiang, Hsin-I (Food science and biotechnology, 2019)
Incidents of food fraud have occurred worldwide, particularly in the form of meat adulteration. In this study, molecular probes were developed using the Random amplification of polymorphic DNA (RAPD) polymerase chain reaction (PCR) technique in order to identify three beef subspecies–Holstein, Angus, and Taiwan Yellow Cattle. Four RAPD-PCR 10-nucleotide primers were chosen out of a total of 60 primers. The selection was based on the reproducibility of species-specific amplicons able to detect various origins of cattle breeds. The results demonstrated that primer OPK12 produced three unique amplicons (1100 bp, 1000 bp and 480 bp) in Holstein; primer OPK14 generated one amplicon that only appeared in Holstein and Angus (200 bp); primer OPK19 amplified two species-specific amplicons in Holstein measuring 550 bp and 650 bp, respectively. However, due to the relatively lower repeatability of RAPD-PCR, higher and more specific testing repeats were required to increase the accuracy of the conclusion.